CLINICAL CHARACTERISTICS OF CHILDREN AND TEENAGERS WITH HEARING IMPAIRMENT ASSISTED AT A REFERENCE INSTITUTION OF THE NORTE FLUMINENSE, RIO DE JANEIRO (Fiep Bulletin - online, 2013)
In Brazil, the IBGE census in 2000 revealed a population of about 6 million hearing impaired. In 2005, the IBGE showed that the occurrence in children up to nine years was about 205,366 cases. According to the Brazilian Society of Otology, it is estimated that 3-5 children per 1,000 are born deaf. Thus, this study describes the clinical characteristics of children and adolescents with hearing impaired treated in a Reference Institution of the Norte Fluminense. We conducted a cross-sectional study, descriptive primary basis, with the population of children and young with hearing impaired, from 7 to 19.9 years in August 2010-2012. Interviews were conducted with parents and/or legal guardian, in person or by telephone, using a previously tested form. Of the 26 children and adolescents evaluated, 61.5% were male, and had a mean(±SD) age of 11.8±3.5 years. As for the medical diagnosis made ??at the first consultation, we detected 42.3% of children and adolescents presenting with profound bilateral sensorineural hearing impairment. Of the participants, 61.5% had no family history of deafness, 23.1% had a family history of deafness. As for the age of diagnosis of deafness, we detected a mean(±SD) age of 2.9±3.0 years. It is concluded that most tested showed profound bilateral sensorineural hearing impairment, medical diagnosis at first visit. The development of new studies is essential to think of strategies for health and adequate nutrition and broad reach to the reality of the group attended.
Keywords: Deafness; Hearing loss; Hearing impaired persons.